Proposta de um novo índice de qualidade de água para Lagoa Salomé através da análise de componentes principais - Mendonça, Maria Caroline Silva (2017)
The knowledge of water quality and its contents are essential to track any influx of water pollutants that are harmful to human health and ecosystems. This study has, then, as objective to propose a new water quality the reservoir Lagoa Salomé, using the principal component analysis. From the principal component analysis, the variables considered critical according to their contributions to the determination of each major component will be extracted for the modification of the reservoir water quality index. The parameters of water quality of these reservoirs will be compared with the limits established by CONAMA’s Resolution nº. 357/2005 and the quality of its water will be determined according to four indexes, commonly used - IAQR (IAP), O-WQI, PW-WQI and CPCB-WQI – and the new proposed index, in order to minimize subjectivity and improve the credibility of the final evaluation. The results for the IQAR, O-IQA, CPCB-IQA and IQAR-m allowed classify the reservoir, respectively, as extremely polluted, very bad, very bad and very polluted. The principal component analysis showed that was possible to reduce the number of variables from 15 to 7 (DO, BOD, N-NO3, Total-N, Total-P, depth and Secchi disk, like the anthropogenic activities, resulting from dumping of domestic and solid residues in the surroundings of Lagoa Salomé, possibly, the main and most significant sources of pollution. Thus, it is important to complete and emphasize that the reservoir water is not in accordance with standards established by CONAMA's Resolution nº. 357/2005 for Class 2 quality, so, a program of environmental monitoring and management is part of the requirements of sustainable development of the region.